Injury incidence and prevalence among elite weight and power lifters - Raske, A.; Norlin, R. (The American Journal of Sports Medicine, 2002)
The purpose of this study was to investigate the incidence and prevalence of injuries among elite weight lifters and power lifters, with a special focus on shoulder injuries and possible injury-provoking exercises. In 1995, a questionnaire was administered to 110 male and female elite lifters to evaluate injuries and training characteristics. A follow-up of the athletes from 1995 was conducted in 2000, and a new 2000 elite group was also queried. In 1995 and again in 2000, the athletes sustained, on average, 2.6 injuries per 1000 hours of activity. Most common in 1995 were low back injuries, with an injury rate of 0.43 per 1000 hours, and shoulder injuries, with a rate of 0.42 per 1000 hours. Shoulder injuries dominated in 2000, with an injury rate of 0.51 per 1000 hours of activity. There was a difference in injury pattern between weight lifters, who mostly sustained low back and knee injuries, and power lifters, in whom shoulder injuries were most common. No correlation was found between shoulder injuries and any specific exercise. Although the total injury rate was the same during the two periods of study, the rate of shoulder injuries had increased.